ENRICHING LOCAL CULTURES THROUGH JAVA CULTURE MISSION LEADING TO SOCIAL INTEGRATED IN TRANSMIGRATION REGION OF TAPUNG KAMPAR RIAU ( An Anthropology Study to Ocu People Cultures) - Syafrizal Syafrizal (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2021)
This study is aimed at exploring a social issues related to enriching local cultures through cultural mission of Java leading to social integrated on transmigration region of Tapung Kampar Riau. This matter is an empirically research as one of important issues for having recommendation in dealing with emerging ones thinking sense to sharpen among the sides.It is noted that transmigration issue is not primary to this study, although transmigration issue must be never neglected, since in this line of program found migration of human from Java people with cultures in huge from Java island into Tapung Kampar Riau.It is truly, human and cultures is something unseperatable at once. By migration of human, it means also migration of cultures as civilization order to the human itself. This study is conducted in qualitative approach. In collecting the data, perhaps done by interview in depth to many informants adopted bases to their capability , expert, figure in public as well as. This study was completed in KecamatanTapungKabupaten Kampar Propinsi Riau,for more than 6 months in execution. Still, make certain analysis, by this research found an enriching local cultures found on Ocu people community through own culture mission of Java leading to a social integrated community mainly around transmigration region where Ocu people live of Tapung Kampar Riau. This matter has been proved with manifested acculturation of both culture on this region either viewed from cultural, sense of feeling, and sensitivity with sense of touch to food and meal, and also in choosing wear of cultural dress, clothes and uniform among the people.